Exploring the role of Germanium on the optoelectronic and thermoelectric response in making ductile lead-free perovskite halide using DFT - Umair Mumtaz; Saira Kiran; Sarfraz Ahmad; Fayyaz Hussain; Syed Awais Rouf; R M A Khalil; Manawwer Alam; Rizwan Wahab; Muhammad Fahad Ehsan (Materials Research Express)
The structural instability observed owing to Sn ^2+ and the toxic effects of lead has prohibited the commercial use of all inorganic CsPb _1-x Sn _x Br _3 for optoelectronic memory device applications. In this work, we have inspected the structural, mechanical, electronic, optical, and thermoelectric response of all inorganic halide perovskite CsPb _1-x Ge _x Br _3 (x = 0, 0.25, 0.50, 0.75, 1) to overcome the stability and toxicity of this optoelectronic resistive switching material using the full-potential linearized augmented-plane wave (FP-LAPW) method grounded on density functional theory (DFT). Tran–Blaha-modified Becky-Johnson (TB-mBJ) approximation is used for the self-consistent field (SCF) calculations of considered halide perovskite CsPb _1-x Ge _x Br _3 . It is clear from the band structure that all compounds are semiconductors in nature. Moreover, the bandgap decreased with the increase in the concentration of Germanium (Ge) causing the bandgap tuning. The overall absorption of incident radiations increased and energy loss decreased with the increase in doping concentration, especially in the visible region. The thermoelectric properties have also been studied by using the BoltzTraP2 code. All the results computed physical properties confirmed the feasibility of these all-inorganic materials for their use in the fabrication of ductile, optical resistive switching memory RRAM devices.